MODELING THE PROCESS OF HEATING FISH RAW BEFORE VACUUM DRYING - Alexander Anatol’evich Yashonkov (Современная наука и инновации)
The paper provides the results of computer simulation of the process of non-stationary heat transfer during the warming up of raw fish in the ANSYS software complex. The duration of heating to the required temperature was estimated.